Edison the wizard of light - Devine, David; Mozer, Richard; Conkie, Heather; Welsh, Kenneth; Suchanek, Michal; Collins, Jesse; Storch, David; Hoffman, Susannah, 1962-; Devine Entertainment Corporation; Merlin Films ([Toronto] : Devine Entertainment Corp., 2001)
Edison takes a truant twelve year-old under his wing and they work together on creating the first motion pictures.
Originally broadcast as an episode of the HBO television program The inventors' specials.
Copyright date on title frames: 1998.
Special features include: The life and times of Thomas Edison; full music soundtrack.
Co-producer Kieran Corrigan ; director of photography, Rick Maguire ; editors, Jeff Warren, Mike Lee, Rik Morden ; music composer, Lou Pomanti.
Kenneth Welsh, Michal Suchanek, Jesse Collins, David Storch, Susannah Hoffman.
DVD; Dolby Digital stereo.
Keywords: Edison, Thomas A. -- 1847-1931 -- Drama; Inventors -- Biography -- Drama; Motion picture projectors -- History -- Drama; Inventors; Inventos; Projectors -- History -- Drama; Video recordings for hard of hearing people; Biographical television programs; Television programs for children